Badania ankietowe – kwestionariusz ankiety – uzasadnienie metodologii ………. 143 - Pasiut, Judyta (Wybory prezydenckie w Polsce w 2025 roku w świadomości najmłodszego elektoratu województwa małopolskiego, 2025)
Survey Research – Survey Questionnaire – Justification of the MethodologyThe aim of the chapter Survey Research – Survey Questionnaire – Justification of the Methodology is a detailed discussion of the survey questionnaire, which is the basis for research conducted among adult students of selected secondary schools in the Lesser Poland voivodeship, regarding the participation of the youngest electorate in the elections of the President of the Republic of Poland in 2025, as well as their knowledge about the institution of the President of the Republic of Poland, the presidential elections in general and the electoral participation. Special attention was paid to the scientific reflection on the applied research methodology in terms of its practicality and popularity in the field of social sciences. The chapter also highlights the hypothesis and research theses, which were verified at the stage of analyses of the conducted scientific research.